Youth Development Agencies: A Case Study of Young People's Experiences in Ekurhuleni Municipality - Nkosi, Mduduzi (Department of Sociology, 2024)
‘Youth unemployment' and ‘youth development' are topical issues in post-democratic South Africa. The country sees an ever-increasing number of predominately working class young people struggling to find ways to ‘enter the economy' over time because of a variety of reasons. South African government has for a while now, taken a reactive role in trying to remedy the situation through various policy interventions. While much has been said about the State's active role, the voices who should arguably be the most important actors, i.e., ‘the recipients' of said development, have been notably absent in the discussions of youth development. It is the aim of this study to give them a voice and to understand how they view youth development and its track record in the country. Using qualitative interviews, the study sought to understand the experiences and perceptions of working age young people in a semi-urban setting when it comes to youth development policy and accessing state funded youth development organizations. It paints a picture of young people who are largely unsatisfied with their government and its efforts to help them become economically active. The findings suggest that young people are mostly unsatisfied with the efforts by the State towards youth development, and feel that the state could do more to help them. The findings also reveal experiences of varied success with getting help from Statecontrolled youth development entities contribute to this view.